Putusan Pengadilan Tanpa Perintah Penahanan Berdasarkan KUHAP dikaitkan dengan Pelaksanaan Eksekusi - Toto Santosa (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2016)
Article 197 paragraph (1) letter k Criminal Procedure Code states that the sentencing decision letter includes a requirement that the defendant be detained or kept in custody or released. Article 197 paragraph (1) letter k Criminal Procedure Code in practice many remained unfulfilled by the Judges in itsdecision, because there is a Judge's decision that declared the defendant guilty of committing a crime , but the verdict is not ordered that the defendant be detained. Article 197 paragraph (1) letter k Codes material ever tested in the Constitutional Court. After the release of the decision of the Court was still there is controversy about the decision of the court without a restraining order associated with the execution. The research specifications used are descriptive analytical, which is to provide data or images as thoroughly as possible about humans, circumstances or other symptoms. The research approach is a normative juridical approach, namely a method that emphasizes research on library data, or called secondary data through legal principles and legal comparisons. This research was conducted in one stage, namely library research. The technique in collecting data uses document studies. Normative-qualitative data analysis. The study found that court decisions in criminal cases need to be stated that the defendant is detained, or remains in detention orreleased as part of a clause to confirm the defendant's status is guilty and must be punished, even though it is not mandatory (since the Constitutional Court's decision) . Execution of court decisions that have permanent legal force, the prosecutor must immediately carry out the execution even though in the court ruling there is no statement of detention order. Court decisions that have obtained permanent legal force in criminal cases, which do not contain a detention order are still valid and do not result in the court decision being null and void by law, so the prosecutor as executor can carry out the execution of court decisions that have obtained permanent legal force.